A comparative study on tobacco use among school boys in single sex and co-education school in Bengaluru - Rajeshwari, Swetha; Nawaz, Ayesha; P., Sathyanarayana; Kurre, Bhaskar (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescent boys are more inclined towards risky behaviors like smoking than girls and those who initiate smoking early in life are more likely to continue to smoke as adults. Peers in schools have a major role on influencing, initiating and continuation of smoking among boys. Therefore, the present study was undertaken to compare the prevalence of tobacco use among boys studying in single-sex school and co-education school and to study the factors associated with tobacco use in both the schools. Methods: A comparative study was conducted in two randomly selected high schools in the urban field practice area of the medical institution; one of it being boys only (single-sex) and another co-education (co-ed) school. All the students studying in 8th, 9th and 10th standard were included in the study. A self-administered, pretested, structured questionnaire adapted from the WHO youth tobacco questionnaire was used to collect the data on tobacco usage, knowledge and attitude along with socio-demographic profile. Data was entered into Microsoft excel and analyzed using EPI info 6. Results: A total of 467 boys participated in the study. Over all prevalence of tobacco use was 21.8% from both the schools. Tobacco use was found to be more in boys’ school 68 (25.7%) when compared to co-education school (16.8%). Prevalence of smoking was found to be 38 (14.4%) and 17 (8.4%) in the two schools, this difference was found to be statistically significant with χ2=4.59, p=0.032. Conclusions: Vulnerability of boys to smoking and risky behaviours in general, more so in single sex schools need to be emphasized and apt interventions designed to prevent its use among boys in various settings ought to be explored.